The impact of transfer pricing on tax avoidance with foreign ownership as a moderating variable: Evidence from Vietnam - Nguyen, Giang Thi Cam; Nguyen, Duy Thanh (Asian Journal of Economic Modelling, 2025)
With the rise of globalization and the proliferation of multinational enterprises, transfer pricing practices have become increasingly complex and contentious. This issue has become particularly significant in the context of developing economies, including Vietnam, where special incentives with flexible mechanisms are considered key to creating an attractive investment climate for foreign investors. Arising from this, the study investigated the relationship between transfer pricing and tax avoidance in Vietnam from 2020 to 2023. The study sampled 217 industrial companies listed on the Hanoi Stock Exchange and the Ho Chi Minh Stock Exchange and extracted data from the annual reports of these companies. Data were analyzed using descriptive statistics as well as quantitative models. The results revealed that foreign ownership magnifies the relationship between transfer pricing and tax avoidance, suggesting that foreign-owned companies may engage more aggressively in transfer pricing activities to minimize their tax liabilities. Regarding the control variables, company size, company growth, and asset tangibility were positively associated with tax avoidance activities. Lastly, a contribution of this study is the pressing need for policymakers to enhance regulatory oversight and enforcement measures to address transfer pricing abuses.